2006
DOI: 10.1002/mmce.20146
|View full text |Cite
|
Sign up to set email alerts
|

A novel miniaturized feedback LC oscillator for UMTS-type applications in 3D stacked liquid crystalline polymer technology

Abstract: This article presents the design and implementation of a feedback LC oscillator in a novel multilayer laminate-type process technology that uses multiple layers of liquid crystalline polymer (LCP) substrate. The 1.8-GHz oscillator is designed using high-qualityfactor (Q) lumped-element passives that are embedded in the LCP substrate. The oscillator was fabricated on a large area, high Q integrated process technology employing six metal layers with an overall height (thickness) of 0.7 mm. The microstrip-type os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Zhou et al first investigated the integration of a gallium arsenide (GaAs) MMIC switch with MSL in 2002, and then reported the integration of capacitors and resistors on an LCP substrate in 2005 [14,106]. Mukherjee et al studied inductors and bandpass filters embedded in multilayer LCP substrates in 2005 [107], while Bavisi et al reported on LC oscillators embedded in multilayer LCP substrates in 2006 [108]. High-Q-embedded passives on large-panel multilayer LCP substrates were investigated in 2007 [109], which eliminate the effects of pads and through-hole interconnection with the de-embedding method.…”
Section: Chip Integration and Packgingmentioning
confidence: 99%
“…Zhou et al first investigated the integration of a gallium arsenide (GaAs) MMIC switch with MSL in 2002, and then reported the integration of capacitors and resistors on an LCP substrate in 2005 [14,106]. Mukherjee et al studied inductors and bandpass filters embedded in multilayer LCP substrates in 2005 [107], while Bavisi et al reported on LC oscillators embedded in multilayer LCP substrates in 2006 [108]. High-Q-embedded passives on large-panel multilayer LCP substrates were investigated in 2007 [109], which eliminate the effects of pads and through-hole interconnection with the de-embedding method.…”
Section: Chip Integration and Packgingmentioning
confidence: 99%